Retrospective Evaluation of the Epidemiology and Practice Variation of Dexmedetomidine Use in Invasively Ventilated Pediatric Intensive Care Admissions, 2007–2013 - Benneyworth, Brian D.; Downs, Stephen M.; Nitu, Mara (Frontiers in Pediatrics, 2015)
Objectives: The study assessed dexmedetomidine utilization and practice variation over time in ventilated pediatric intensive care (PICU) patients; and evaluated differences in hospital outcomes between high- and low-dexmedetomidine utilization hospitals. Study Design: This serial cross-sectional analysis used administrative data from PICU admissions in the Pediatric Health Information System (37 US tertiary care pediatric hospitals). Included admissions from 2007-13 had simultaneous dexmedetomidine and invasive mechanical ventilation charges, <18 years of age, excluding neonates. Patient and hospital characteristics were compared as well as hospital-level severity adjusted, indexed length of stay (LOS), charges, and mortality. Results: The utilization of dexmedetomidine increased from 6.2 to 38.2 per 100 ventilated PICU patients among pediatric hospitals. Utilization ranged from 3.8 to 62.8 per 100 in 2013. Few differences in patient demographics and no differences in hospital-level volume/severity of illness measures between high and low utilization hospitals occurred. No differences in hospital-level, severity-adjusted indexed outcomes (LOS, charges, and mortality) were found. Conclusions: Wide practice variation in utilization of dexmedetomidine for ventilated PICU patients existed even as use has increased 6-fold. Higher utilization was not associated with increased hospital charges or reduced hospital LOS. Further work should define the expected outcome benefits of dexmedetomidine and its appropriate use.